Binocular function years after surgery - Reich-d'Almeida, F. (2017)
Purpose - To demonstrate that in surgically treated infantile esotropia patients, with no previous signs of binocularity, it is possible after a very long therapy with medical and orthoptic regular follow up, to achieve functional rehabilitation well above the conventionally accepted age for sensorial recovery.